Hippocampal orexin-1 and endocannabinoid-1 receptors underlie the kainate-induced occlusion in theta-burst long- term potentiation. (October 2022) - Nasudi, Giti; Elahdadi Salmani, Mahmoud; Hosseinmardi, Narges; Moradpour, Farshad; Lashkarbolouki, Taghi; Goudarzi, Iran
Abstract: Introduction: Seizures may result from the hyperexcitable neuronal activity of the brain. Multiple neurotransmitter receptors, including orexin (OX) and endocannabinoids interfere with forming the synaptic responses linked to the seizures. Therefore, this study investigates the involvement of OX-1 (OX1R) and endocannbinoid-1 (CB1R) receptors in the kainate- induced excitability in the synaptic field responses. Material and methods: Theta pattern used to stimulate Schaffer collaterals and then metal microelectrodes to record the CA1 field excitatory postsynaptic potentials (fEPSPs). Input/ output stimulation and responses and paired- pulse (PP) stimuli employed to measure the state of synaptic activity in normal and kainate- induced seizure-like hyperexcitable activities and the slope of fEPSPs used as a measure of the change in the synaptic activity. Furthermore, agonists and antagonists of OX and endocannabinoids infused to investigate the involvement of their receptors. Result: The results showed that kainate application increased the fEPSP slope either in input stimuli with different intensities/output synaptic responses (I/O), or test pulse stimulated baseline synaptic responses (BSR) and, hence, increased the excitability of field responses in the CA1 region. However, neither kainate nor theta burst stimulation (TBS) could alter the PP stimuli -induced synaptic responses. TBS increased the fEPSP slope of the kainate-applied I/O and BSR, however, the increase was not high enough in BSR to be classified as long-term potentiation (LTP). The single-antagonist OX1R and CB1R administration prevented TBS- induced potentiation and partially recovered the effect by adding eCB or OX agonists in kainate-injected animals. In contrast, OX or combined eCB-OX antagonist application group demonstrated nearly full recovery of LTP induction. Conclusion: Our study concludes that blockade of OX1 or CB1 prevents the induction of LTP, and OX infusion or both receptor blockade recovers the LTP. Highlights: Kainate increased the excitability and slope of hippocampal fEPSP responses. Theta burst stimulation (TBS) increased the excitability of the CA1 responses. TBS induced long term potentiation (LTP) was impeded by the kainate application. Orexin or eCB receptor antagonism prevented the TBS-LTP, similar to kainate. Orexin or dual, orexin and eCB, receptor antagonism recovered the capacity for LTP.